Cyclic hypoxia does not alter RAD51 expression or PARP inhibitor cell kill in tumor cells. Issue 3 (September 2015) - Kumareswaran, Ramya; Chaudary, Naz; Jaluba, Karolina; Meng, Alice; Sykes, Jenna; Borhan, Asm; Hill, Richard P.; Bristow, Robert G.
Abstract Solid tumors contain regions of chronic and cyclic hypoxia. Chronic hypoxia can downregulate RAD51 and sensitize cells to PARP inhibition. Herein, we show that RAD51 expression, cell survival and toxicity to PARP inhibition is not affected under cyclic hypoxic conditions. This suggests that PARP inhibition may be selectively toxic in tumor sub-regions associated with chronic hypoxia.